EVALUATION OF TECTONIC STRUCTURE OF İSKENDERUN BASIN (TURKEY) USING STEERABLE FILTERS - Albora A.M.; Sayın N.; Uçan O.N. (My University, 2006)
In this paper, we demonstrate the effectiveness of steerable filters as a method of delineating the boundaries of subsurface geological structures. Steerable filters, generally used for edge detection on 2-D images, have the properties of band pass filters with certain directions and are applied to many image processing problems. We first tested the method on synthetic data and then applied it to the aeromagnetic data of İskenderun Basin and adjacent areas. İskenderun Basin is located in the Northeastern Mediterranean where African–Arabian and Anatolian plates are actively interacting. The basin fill records a complex tectonic evolution since the Early Miocene, involving ophiolite emplacement, diachronous collision of Eurasian and Arabian plates and subsequent tectonic escape related structures and associated basin formation. Geophysical investigations of the tectonic framework of İskenderun Basin of Turkey provide important insights on the regional tectonics of the Eastern Mediterranean and Middle East. In this study we show geological structures, which are responsible for the magnetic anomalies in İskenderun Basin and enlighten the structural setting of the Northeastern Mediterranean triple junction using steerable filters. We obtained a magnetic anomaly map of the region from the General Directorate of Mineral Research and Exploration as raw data and then evaluated this by steerable filters. We determined the magnetic anomaly boundaries for İskenderun Basin by using various types of steerable filters and correlated these to drilling data and seismic profiles from the Turkish Petroleum Corporation. The result of the steerable filter analysis was a clarified aeromagnetic anomaly map of İskenderun Basin. The tectonic structure of İskenderun Basin is divided into regions by an N–S trending oblique-slip fault defined by the steerable filter outputs. We propose a new tectonic structure model of İskenderun Basin and modify the direction of the East Anatolian Fault Zone. In our model, East Anatolian Fault Zone cross-cuts the basin as a narrow fault zone and continues towards the Cyprus arc.
Keywords: STEERABLE FILTERS; AEROMAGNETIC ANOMALY; İSKENDERUN BASIN; EAST ANATOLIAN FAULT ZONE; EDGE DETECTION; Miocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен